The Boundaries of EU Copyright Law: Cheese, Jeans and a Military Report in the Court of Justice - Nuno Sousa e Silva (Market and Competition Law Review)
Copyright is a centrepiece in the ongoing construction of the digital single market. Evidently, copyright only applies to works. Thus, the definition of its scope lies in knowing what a work is. Although that was not envisioned nor intended by the lawmaker, the Court of Justice has adopted a European notion of work in its controversial decision C-5/08, Infopaq, conflating it with the one of originality. Such an approach has been confirmed and expanded by subsequent case law. The Court has already fleshed out the main criterion for a creation to enjoy copyright – it must be original in the sense of being the author’s own creation – and seems to reject any additional criteria. However, the boundaries of the European notion of work are still unknown. Some recent preliminary ruling requests will allow some clarification. One asks about the possibility of copyright protection for the taste of a specific cheese (C-310/17, Levola Hengelo). Another one deals with the protection of a fashion design for jeans (C-683/17, Cofemel) and yet another concerns a military report (C-469/17, Funke Medien). After describing the evolution of the law on the EU notion of copyright, this article frames and critically analyses the questions surrounding these cases, proposes answers thereto and makes a prediction of the outcome, i.e. the Court’s decision, in each of them.